NAFLD and Infection, a Nuanced Relationship - Abimbola Adenote; Igor Dumic; Cristian Madrid; Christopher Barusya; Charles W. Nordstrom; Libardo Rueda Prada (Canadian Journal of Gastroenterology and Hepatology)
The prevalence of nonalcoholic fatty liver disease (NAFLD) has increased significantly over the last few decades mirroring the increase in obesity and type II diabetes mellitus. NAFLD has become one of the most common indications for liver transplantation. The deleterious effects of NAFLD are not isolated to the liver only, for it has been recognized as a systemic disease affecting multiple organs through protracted low-grade inflammation mediated by the metabolic activity of excessive fat tissue. Extrahepatic manifestations of NAFLD such as cardiovascular disease, polycystic ovarian syndrome, chronic kidney disease, and hypothyroidism have been well described in the literature. In recent years, it has become evident that patients suffering from NAFLD might be at higher risk of developing various infections. The proposed mechanism for this association includes links through hyperglycemia, insulin resistance, alterations in innate immunity, obesity, and vitamin D deficiency. Additionally, a risk independent of these factors mediated by alterations in gut microbiota might contribute to a higher burden of infections in these individuals. In this narrative review, we synthetize current knowledge on several infections including urinary tract infection, pneumonia, Helicobacter pylori, coronavirus disease 2019, and Clostridioides difficile as they relate to NAFLD. Additionally, we explore NAFLD’s association with hidradenitis suppurativa.